SHARIA-BASED MSME DEVELOPMENT STRATEGY IN TEBING TINGGI CITY - Lubis, Radja Janna; ,., Sugianto2; Rahmani, Nur Ahmadi Bi (LPPM Universitas Trunojoyo Madura, 2025)
The purpose of this study is to develop a development plan for sharia-based MSMEs in Tebing Tinggi City to encourage more equitable and inclusive regional economic development. This study used a qualitative descriptive method. Five MSMEs that have implemented sharia principles in their operations were observed and interviewed to collect data. The collected data were then analyzed thematically to identify trends, obstacles, and development tactics. The study findings demonstrate that sharia-based MSMEs in Tebing Tinggi City have adopted Islamic values such as being free from usury, using halal materials, and contributing to social welfare. However, they still face significant challenges such as limited access to sharia financing, a lack of Islamic economic literacy, and suboptimal utilization of digitalization. Recommended development strategies include improving sharia literacy, partnerships with Islamic financial institutions, training in digitalization and halal marketing, and facilitating halal certification. An integrative approach based on spiritual values, technology, and institutionalization is needed to strengthen the competitiveness of sharia-based MSMEs sustainably. This study contributes to the strategic framework for sharia-based MSME development at the regional level, integrated with Islamic economic principles and local challenges. The uniqueness of this study lies in the focus on the local context of Tebing Tinggi City and the direct interview approach to formulate sustainable strategies.Keywords: Sharia-compliant MSMEs, development strategy, finance, local economy, Tebing Tinggi City